2022
DOI: 10.1016/j.scitotenv.2021.150376
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of SARS-CoV-2 RNA shedding routes to RNA loads in wastewater

Abstract: A portion of those infected with SARS-CoV-2 shed the virus and its genetic material in respiratory fluids, saliva, urine, and stool, thus giving the potential to monitor for infections via wastewater. Wastewater surveillance efforts to date have largely assumed that stool shedding has been the primary source of SARS-CoV-2 RNA signal; however, there are increasing questions about the possible contribution of other shedding routes, with implications for wastewater surveillance design and feasibility. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 39 publications
1
41
0
Order By: Relevance
“…Our previous meta-analysis summarized the clinical results from around 1500 patients covering all the gender, age groups (children, adults<60 and adults over 60), and pathological conditions (severe, moderate, and mild), which revealed that the mean shedding magnitude was 10 4.523±0.133 gene copies/g, and the mean shedding probability ( P s ) was 0.545±0.093 ( Li et al, 2021b ). Similar values were reported in other meta-level analyses where the positive proportion of the fecal samples was found to be 51.8% (95% CI 43.8-59.7%) and the median shedding concentration was 10 3.4 (95%CI: 10 0.24 -10 6.5 ) to 10 4.9 (95%CI: 10 3.9 -10 6.8 ) ( Crank et al, 2022 , Miura et al, 2021 , van Doorn et al, 2020 ). The detection efficiency of clinical protocol for SARS-CoV-2 RNA in stool samples was confirmed using standardized stool samples (stool samples with no SARS-CoV-2 RNA) spiked with synthetic SARS-CoV-2 RNA, where comparable results to the initial spike-in concentrations were achieved ( Poon and Tee, 2021 ), suggesting that the detected SARS-CoV-2 RNA concentration can largely reflect the actual concentration in stool samples.…”
Section: Methodssupporting
confidence: 89%
See 1 more Smart Citation
“…Our previous meta-analysis summarized the clinical results from around 1500 patients covering all the gender, age groups (children, adults<60 and adults over 60), and pathological conditions (severe, moderate, and mild), which revealed that the mean shedding magnitude was 10 4.523±0.133 gene copies/g, and the mean shedding probability ( P s ) was 0.545±0.093 ( Li et al, 2021b ). Similar values were reported in other meta-level analyses where the positive proportion of the fecal samples was found to be 51.8% (95% CI 43.8-59.7%) and the median shedding concentration was 10 3.4 (95%CI: 10 0.24 -10 6.5 ) to 10 4.9 (95%CI: 10 3.9 -10 6.8 ) ( Crank et al, 2022 , Miura et al, 2021 , van Doorn et al, 2020 ). The detection efficiency of clinical protocol for SARS-CoV-2 RNA in stool samples was confirmed using standardized stool samples (stool samples with no SARS-CoV-2 RNA) spiked with synthetic SARS-CoV-2 RNA, where comparable results to the initial spike-in concentrations were achieved ( Poon and Tee, 2021 ), suggesting that the detected SARS-CoV-2 RNA concentration can largely reflect the actual concentration in stool samples.…”
Section: Methodssupporting
confidence: 89%
“…Thus, considering the shedding probability ( Table 1 ) and the possibility of entering the sewer system, apart from feces, sputum is likely to be an additional major source. A recent study revealed that sputum shedding potentially contributed a great amount of SARS-CoV-2 RNA into wastewater through theoretical simulations ( Crank et al, 2022 ). However, the changes in the prevalence estimation caused by the inclusion of sputum as another shedding source remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, biweekly monitoring of Luxembourg wastewater samples provides an overview of up to 73% of the population (https://www.list.lu/en/covid-19/coronastep/; accessed on 9 June 2021). While SARS-CoV-2 is primarily transmitted through aerosols [2], the virus can also persistently be detected in the urine and feces of infected people [3][4][5]. The presence of this virus in the excreta of infected patients led researchers to question its transmission through the water cycle and its persistence in the environment [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The WBE approach to monitoring COVID-19 is an area of rapid development and thus all the factors defining the minimum threshold number of new COVID-19 cases within a sewer network area for detecting SARS-CoV-2 in the wastewater (WW) influent are not clear. One of the necessary considerations from the clinical standpoint is the variability in shedding quantities (viral load) and secretion routes (feces, urine, cough, sneeze, and sputum) of infected individuals from where virus particles end up in the sewage systems ( Wölfel et al 2020 , Wang et al 2020 , Wu et al 2020, Cevik et al 2021 , Crank et al 2022 ). From the environmental standpoint, the fate and decay of SARS-CoV-2 in sewer networks and transit after sampling before analysis are not fully known ( Hart and Halden 2020 , Kitajima et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%